Structural evolution of the emerging 2014-2015 GII.17 noroviruses - Singh, Bishal; Koromyslova, Anna D.; Hefele, Lisa; Gürth, Clara; Hansman, Grant S. (Journal of virology, 2016)
Recent reports suggest that human genogroup II genotype 17 (GII.17) noroviruses are increasing in prevalence. We analyzed the evolutionary changes of three GII.17 capsid protruding (P) domains. We found that the GII.17 P domains had little cross-reactivity with antisera raised against the dominant GII.4 strains. X-ray structural analysis of GII.17 P domains from 2002 to 2014 and 2015 suggested that surface-exposed substitutions on the uppermost part of the P domain might have generated a novel 2014-2015 GII.17 variant.